An Analysis of Students' Mathematical Communicative Skills in Solving Sets Problems at SMP Negeri 1 Darul Hikma Aceh Jaya - Rizka Mahdalela; Nur Ainun; Roslina Roslina (Universitas Serambi Mekkah, 2022)
This study aimed to determine the description of students' mathematical communication skills in solving problems in set material, especially students' written mathematical communication skills. This type of research is descriptive using a qualitative approach. The research subjects were taken from class VII students of SMPN 1 Darul Hikmah. Subject taking was carried out by looking at the value of the report card which was then selected by 3 research subjects based on the existing categories. The instrument used is a written test of mathematical communication skills which contains 3 essay questions with set material and interview guidelines. The interview guide is aimed at subject teachers to find out whether students already know mathematical communication skills. Written mathematical communication skills contain 5 indicators. The results showed that the written mathematical communication skills of the research subjects were good for indicators of ability and in writing the information contained in the questions and determining the main goals to be achieved. However, the research subjects were weak in writing mathematical operations according to the intent of the questions using pictures or scientific notation in solving problems, presenting a comprehensive representation of the concepts used and writing conclusions about answers in everyday language. The results of this study are expected to gain and add insight into the written mathematical communication skills of students of SMP Negeri 1 Darul Hikmah, Aceh Jaya district, on set material, especially in mathematics. So that thus being able to improve the ability to communicate in the language of mathematics in solving problems of everyday life. Keywords: Mathematical Communication Skills, Solving Problems, Set Material